2006
DOI: 10.1063/1.2337085
|View full text |Cite
|
Sign up to set email alerts
|

Prospective emission efficiency and in-plane light polarization of nonpolar m-plane InxGa1−xN∕GaN blue light emitting diodes fabricated on freestanding GaN substrates

Abstract: Prospective equivalent internal quantum efficiency ͑ int ͒ of approximately 34% at 300 K was demonstrated for the blue emission peak of nonpolar m-plane ͑1100͒ In x Ga 1−x N / GaN multiple quantum well light emitting diodes ͑LEDs͒ fabricated on freestanding m-plane GaN substrates. Although the int value is yet lower than that of conventional c-plane blue LEDs ͑Ͼ70% ͒, the results encourage one to realize high performance green, amber, and red LEDs by reducing the concentration of nonradiative defects, accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 30 publications
2
54
2
Order By: Relevance
“…Consequently, it results in reduction of quantum efficiency of light-emitting diodes. 2 A way to overcome this deficiency is to grow GaNbased QWs along nonpolar orientations, for example, m plane 3,4 or a plane. 5,6 It has been shown that the electric field can be avoided in such nitride QWs.…”
mentioning
confidence: 99%
“…Consequently, it results in reduction of quantum efficiency of light-emitting diodes. 2 A way to overcome this deficiency is to grow GaNbased QWs along nonpolar orientations, for example, m plane 3,4 or a plane. 5,6 It has been shown that the electric field can be avoided in such nitride QWs.…”
mentioning
confidence: 99%
“…For common GaN LED structures grown along the c axis, access to this polarized light can only be gained by measurements taken from the edge of the sample [19][20]. Several authors have reported polarized light emission for LED structures grown on nonpolar or semipolar GaN substrates [21][22]. In the present study, we investigate the approach employing photonic crystals (PhCs) which do not require the growth on different orientation of sapphire or GaN substrates nor using specific wafer orientations.…”
Section: Polarized Light Emission Properties Of Gan-based Photonic Crmentioning
confidence: 99%
“…It originates from the built-in electric fields along the [0001] direction separate the electron and hole wave functions in a quantum well (QW) thereby reducing the recombination probability of electron-hole pairs. In order to eliminate these polarization effects, one alternative way is to grow non-polar, e.g., (the a-plane) GaN thin films and InGaN/GaN QWs along unconventional non-c-axis directions 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The m-plane InGaN/GaN multiple quantum wells (MQWs) have been synthesized substrates by molecular-beam epitaxy(MBE) 4 and LED structures have been grown by metal-organic chemical vapor deposition (MOCVD) on LiAlO 2 [LAO] (100) 5,6 , recently. This non-polar plane GaN will exhibit intrinsic in-plane anisotropy even in the unstrained case due to the broken hexagonal symmetry.…”
Section: Introductionmentioning
confidence: 99%